Баня, сауна, бассейн своими руками - Синельников Владимир (Строим и ремонтируем сами из того, что под руками, 2008)
Экземпляры: (20240318) / Инвентарный номер: 43411 / Цена: 60.70 / Сис.шифр: 38.6 / Авт.знак: Б 23 / ГРНТИ: 67 / ББК: 38.6